Credit enhancement and bond rating: An empirical study of the bonds issued by local government financing platforms. Issue 1 (20th February 2017) - Hu, Yiming; Yang, Ying; Han, Pengfei
Abstract : Purpose: The purpose of this paper is to examine the difference of credit enhancement of variously secured bonds issued by local government financing platform bond (LGFPB). Design/methodology/approach: The approaches to secure the bonds usually include mortgage, collateral, guarantee, etc. Findings: Using a sample of LGFPBs issued during the 2007-2013 period, the authors find that all of the approaches to secure the bonds would increase the bond rating and that compounded approaches have a higher credit enhancement effect than single approaches. Among these approaches, the requirement of collateral has the strongest enhancement effect. Moreover, the authors find that the guarantee provided by a state-owned bank or enterprise increases the bond rating more than the guarantee provided by other local government financing platforms. Research limitations/implications: The findings in this study suggest that the credit enhancement would be deeply affected by the approach used to secure the bond. Practical implications: These results can help the local government make better decisions when issuing bond. Originality/value: This study empirically analyzes the different credit enhancement approaches for securing LGPFBs for the first time and contributes to the literature regarding credit ratings of local government bonds.